Schutz vor Diskriminierungen in dem Bereich der Beschäftigung in dem Polnischen und in dem Deutschen Recht im Licht der Europäischen Richtlinien - Nowakowska-Gancarz, Justyna (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
'The protection against discrmination practices in the field of employment in resp﻿e﻿c﻿t﻿ ﻿o﻿f﻿ ﻿﻿P﻿o﻿l﻿i﻿﻿﻿sh﻿﻿﻿ ﻿a﻿n﻿d﻿ ﻿﻿G﻿e﻿r﻿m﻿a﻿n﻿ ﻿l﻿a﻿w﻿ ﻿i﻿n﻿ ﻿t﻿h﻿e﻿ ﻿l﻿i﻿g﻿h﻿t﻿ ﻿﻿﻿﻿﻿﻿﻿﻿﻿﻿﻿﻿o﻿f﻿ ﻿﻿E﻿U﻿ ﻿d﻿i﻿r﻿e﻿c﻿t﻿i﻿v﻿e﻿s﻿﻿'﻿ The article is devoted to the subject of non-discrimination regulations during employment in respect of Polish and German law.The thesis examines the legal basis of non-discrimination and equality in employment and occupation with reference to European Union law. Regulations against workplace discrimination are included in primary and secondary sources of European Union legislation. The fundamental regulations for countering discrimination are European directives, which forbid discrimination based on race, ethnic origins, religion, beliefs, disability, age, sexual orientation and other listed grounds for hiring, firing, job advertisements and other terms and conditions of employment.Directives are implemented by the EU member states. According to the Treaty on the Functioning of the European Union they are free to choose the form and methods of implementation in a way that ensures the most effective protection against discrimination. Implementation of the EU anti-discrimination directives in Poland was executed by amending Polish labour law, while Germany decided to transpose them through the establishment of new regulations - the General Equal Treatment Act.The paper presents definitions of different forms of discrimination (e.g. direct, indirect), exceptions to anti-discrimination legislation and other issues related to protection against discrimination in German and Polish law.
Keywords: ochrona przed dyskryminacją; zatrudnienie; prawo polskie; prawo niemieckie